Surface lg on B lymphocytes from cattle and sheep - Naessens, Jan (Oxford University Press, 1997)
IgD, first demonstrated in humans, has been unequivocally shown to exist in primates and rodents. In addition to lgM a second unique membrane isotype, generally considered to be lgD, has been demonstrated in a number of other species, including dogs and chickens. Because of its assumed widespread presence, it is widely accepted that lgD is phylogenetically conserved and therefore functionally important in B cell maturation. In the present paper, we could not demonstrate lgD on bovine B cells derived from peripheral blood, lymph nodes, spleen and fetal spleen by precipitation with anti-light chain antibodies. This lack of detectable lgD was confirmed in peripheral blood B cells of sheep, and raises questions on the requirement for lgD in cell differentiation and lg secretion. At present it is not clear whether cattle (and sheep) are an exception in this context. Reports of the presence of lgD in different species are largely based on the assumption that non lgm surface lg is most likely lgD. The data question this extrapolation and stress the need for further isotype characterization of the surface lg in different species. Lack of surface lgD has been observed in human and mouse B-1 cells, most of which express the surface marker CD5. The possibility that all bovine B cells belong to the B-1 lineage is discussed.